2014
DOI: 10.1186/1742-2094-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of TRIM21 in the type-I interferon pathway in Japanese encephalitis virus-infected human microglial cells

Abstract: BackgroundJapanese encephalitis virus (JEV) infection leads to Japanese encephalitis (JE) in humans. JEV is transmitted through mosquitoes and maintained in a zoonotic cycle. This cycle involves pigs as the major reservoir, water birds as carriers and mosquitoes as vectors. JEV invasion into the central nervous system (CNS) may occur via antipodal transport of virions or through the vascular endothelial cells. Microglial cells get activated in response to pathogenic insults. JEV infection induces the innate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 52 publications
1
76
0
Order By: Relevance
“…However, the survivors still show neurological and cognitive impairments [31]. JEV has been reported to evade the innate response of host and establish pathogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the survivors still show neurological and cognitive impairments [31]. JEV has been reported to evade the innate response of host and establish pathogenesis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid cells, including both tissue and lymphoid DCs and macrophages, are primary target cells for JEV infection and regulate the spread of a virus to distant tissues such as the CNS [7,8]. In addition, myeloid cells can produce IFN-I proteins (IFN-α/β) via PRR recognition upon JEV infection, which plays a crucial role in controlling viral replication at the periphery [16][17][18][19][20]. Because virus load at the periphery of 4-1BB KO mice was lower than that of wild-type BL/6 mice in the present study, we assessed whether 4-1BB signaling would affect JEV replication and IFN-I innate response in myeloidderived cells as primary target cells, in order to further define the role of 4-1BB signaling in controlling JE progression.…”
Section: Potent Ifn-i Innate Response Of 4-1bb Signal-deficient Myelomentioning
confidence: 99%
“…While JEV-specific T cells and virus-neutralizing IgM and IgG are considered to participate in the clearance of virus from both peripheral lymphoid tissues and the CNS [11], innate immune responses appear to play a more crucial role in the early control of JEV infection, due to delayed establishment of adaptive immunity. The type I IFN (IFN-I; typically IFN-α/β) innate immune response is essential for controlling various viral infections, including JEV [12][13][14][15], and IFN-I production is triggered by recognition of viral pathogen-associated molecular patterns (PAMPs) through cytoplasmic helicases (RIG-I, MDA5) and Toll-like receptors (TLRs) [16][17][18][19][20]. In addition, recent data indicate that type II IFN (IFN-II; only member IFNγ) produced by NK and CD4 + Th1 cells has a beneficial effect on disease outcomes after JEV infection [21,22], although the requirement for IFN-II in recovery from infection with different flaviviruses varies [21,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…TRIM family proteins participate in a wide range of biological processes, such as cell growth, migration, differentiation, apoptosis, and immunity 5, 6, 7, 8. In the past few years, the role of TRIM proteins received much attention regarding innate immunity to viral infections 9. Recently, researchers found that TRIM proteins also serve as oncogenes or tumour suppressors implicated in various cancers, including GC.…”
Section: Introductionmentioning
confidence: 99%